Implementasi Media Rolling Bottle Terhadap Peningkatan Kemampuan Membaca Anak TK A Putri Muslimat NU 15 Lamongan - Nur Hidayatur Ruchmana; Winnuly Winnuly; Lila Hikmawati (AJER: Advanced Journal of Education and Religion, 2024)
Interesting learning media and creative teachers are the main factors in stimulating children, especially in reading ability, this is included in the background of the preparation of this thesis. Judging from the observation results, there are still many children who do not fully know consonants/vowels, as well as understanding sentences/words due to the lack of learning media to improve their reading skills. Researchers carry a new media called a rolling bottle in learning activities to stimulate the improvement of children's reading skills. The media is a game to improve children's reading skills by using bottles rolled on paper which each has a variety of writings such as consonants, vowels, and sentences/words. The objectives of this study are: (1) To find out the implementation of rolling bottle media on improving the reading ability of group A children of Muslimat Kindergarten NU 15 Lamongan, (2) To determine the improvement of the reading ability of group A children of Muslimat Kindergarten NU 15 Lamongan by using rolling bottle media. This research is a classroom research and the data collection techniques used are observation, interviews, documentation, and tests. The success criteria of this study are the percentage of student completion reaching 90% and the average group score reaching 85. The results of this study showed that there was an increase in children's reading ability by using rolling bottle media with the qualification of Developing According to Expectations (BSH), as evidenced by the percentage of completeness of learning outcomes in the pre-cycle of 15.7% to 26.3% in the first cycle, and increased again to 94.7% in the second cycle. Meanwhile, the average score of the group in the pre-cycle got an average score of 50.3, then the first cycle got an average score of 53.7 and the second cycle got an average score of 85.7. The suggestion that can be given is that teachers should make this rolling bottle media a medium to improve children's reading skills and not only fixated on the media of books/fairy tales, teachers are expected to be more creative in providing stimulation in every learning activity, especially in reading learning activities.